Speech patterns in Cypriot Greek late talkers - Petinou, Kakia; Okalidou, Areti (My University, 2006)
The investigation longitudinally examined the phonetic skills of Cypriot-Greek children with late onset of expressive vocabulary. The rate of phonological development within short time increments and the identification of possible speech constraints motivating slow development of expressive language were examined. Participants were seven Cypriot-Greek children identified as late talkers, and seven age-matched normally developing counterparts. Phonetic skills were examined at ages 30, 33, and 36 months for both groups based on spontaneous language samples. Phonological analyses focused on the construction of all subjects’ phonetic inventories over time. Both groups exhibited an increase of specific phoneme use over time. Late talkers had significantly poorer phonetic inventories when compared to the control group. Within the experimental group the analysis revealed the persistent omission of word-initial consonants. Results are discussed in terms of language-specific phonological constraints and their relation to slow development of speech.
Keywords: Speech patterns; Cypriot - Greek; Late speekers; Phonetic skills